What is wrong with this proof?

2 = 1

a = b

a^{2} = ab

a^{2} – b^{2} = ab – b^{2}

(a + b) (a – b) = b (a – b)

a + b = b

2b = b

2 = 1

Please follow and like us:

What is wrong with this proof?

2 = 1

a = b

a^{2} = ab

a^{2} – b^{2} = ab – b^{2}

(a + b) (a – b) = b (a – b)

a + b = b

2b = b

2 = 1

Please follow and like us:

Right, this is a nice beginning but i’ll have to consider that a tiny bit more. Will show you what else i have found.

u cant cancel (a-b=0) from both sides. if u could no need of such a long procedure.

999999999999999*0=1*0

then, 9999999999999999=1 ???? 🙂

(a + b) (a – b) = b (a – b) after this we can’t write a + b = b

because a-b=0